The progress of school education in India - Geeta Gandhi Kingdon (GPRG-WPS-071, 2007)
This paper provides an overview of school education in India. Firstly, it places India.s educational achievements in international perspective, especially against countries with which it is now increasingly compared such as BRIC economies in general and China in particular. India does well relative to Pakistan and Bangladesh but lags seriously behind China and the other BRIC countries, especially in secondary school participation and youth literacy rates. Secondly, the paper examines schooling access in terms of enrolment and school attendance rates, and schooling quality in terms of literacy rates, learning achievement levels, school resources and teacher inputs. The substantial silver lining in the cloud of Indian education is that its primary enrolment rates are now close to universal. However, despite progress, attendance and retention rates are not close to universal, secondary enrolment rates are low, learning achievement levels are seriously low and teacher absenteeism is high, signalling poor quality of schooling. Thirdly, the paper examines the role of private schooling in India. While more modest in rural areas, the recent growth of private schooling in urban areas has been nothing short of massive, raising questions about growing inequality in educational opportunity. Evidence suggests that private schools are both more effective in imparting learning and do so at a fraction of the unit cost of government schools, their cost advantage being because they can pay market wages while government school teachers. bureaucratically set minimum wages have large rents in them which teacher unions have fought hard to secure. Lastly, the paper discusses some major public education initiatives such as Sarva Shiksha Abhiyan, mid-day meal and para-teacher schemes. The impacts of these massive interventions (and their sub-components) on children.s schooling outcomes need to be rigorously evaluated to learn about the cost-effectiveness of alternative interventions for better future policy making. However, the existence of some of these initiatives and the introduction of the 2 per cent education cess to fund them suggests increased public commitment to school education and, together with increased NGO education activity, gives grounds for optimism about the future, even though many challenges remain.